Determining the mental model of experts regarding the factors hindering the development of table tennis in Iran - Famileh, Maryam Zeinal (2021)
Determining the mental model of experts regarding the factors hindering the development of table tennis in Iran. The purpose of this study is to determine the mental pattern of experts regarding the barriers to professional table tennis in Iran using Q methodology. The present study is applied in terms of purpose; In terms of exploratory nature; In terms of data collection, descriptive-survey, and due to application, Q methodology is a type of mixed research (quantitative-qualitative). The statistical population was veterans and elites in table tennis in Iran, from which 21 people were selected as participants through a combination of purposeful and unlikely sampling and snowball sampling. Participant sorting data were entered in SPSS software to identify the different mindsets of the participants using Q-factor analysis. Finally, the main deterrents in Iranian professional table tennis were prioritized based on nine mental patterns. These mental patterns were then discussed and interpreted. Finally, coping strategies were proposed.